A Connotative Meaning Analysis of Journalistic Language on Tribunnews online.com(Politic Issues) - Duwi Jayanti; Asridayani Asridayani; Rini Afrilesa J (Krinok:Jurnal Linguistik Budaya, 2019)
This research studies about connotative meaning that found in journalistic language. The aims of this research are to explain the connotative meaning and to find out the kinds of connotative meaning of journalistic language on Tribunews online.com (Politics Issues) which the result concluded based on Leech’s (1981) and Parera’s (2004) theories.The method that used in this research is descriptive – qualitative method which is all data analyzed in non-statistical. The data is analyzed through referential technique which is the tool device is outside. In this research, the writer do not involved in the appearance the data, the writer only becomes observers and does the research by downloading and classify the news articles about politic which contain connotative meaning. The results of this research showed that each use of connotative meaning in writing journalistic language can stimulate the reader’s feeling, either stimulate positive or negative stimulation. The writer found mostly the using of connotative is negative connotation which can be seen there are 11 negative connotations and 7 positive connotations of 18 data consist of words and phrases. Keyword: Connotative Meaning, Journalistic Language, and Politic Issues.